دراسة بيئية لبعض الخواص الفيزيائية والكيمائية لمياه بعض الأهوار في محافظة ذي قار- جنوب العراق - السعيدي, صباح ناهي (University of Thi-Qar Journal of Science, 2014)
A study was conducted on some physical and chemical properties of some marshes water ( Abu - Zurik , AlSanaf and Al- Adel ) at Thi - Qar governorate to know the changes that were happened on the ecological factors of water. Water samples were collected from the studied marshes along one year from January to December 2010 . The study were included the estimation values of ( pH ) and concentrations of electrical conductivity (EC) , total dissolved solid (TDS) , total hardness (TH) , dissolved oxygen (DO) , chemical oxygen demand (COD) , turbidity (T) and the concentrations of positive mineral ions ( Ca+2 and Mg+2 ) and negative ( Cl -1 , PO4 -3 , NO3 -1 and SO4 -2 ) that were estimated by mg / l . The results of the study were showed a difference on the marsh water properties during the months of the year , and a clear differences between water properties of the studied marshes were noticed also , it was found a clear significant differences between water properties of its water . From the study it was illustrated that , water of the studied marshes trended to alkalinity and high salinity percentages and semi hardness that was not suitable for drinking and other uses for humanity depending on their studied properties , which were the concentrations of its properties that measured more than the ecological limited concentrations of the suitable water for uses to human .